Influence of diatom-amorphous silica on strength and durability of steel slag and cement-treated clays - Joyce Nakayenga; Nozomi Omaki; Daehyun Kim; Toshiro Hata (Soils and Foundations)
Steel slag, a by-product of steel making, is increasingly used in geotechnical construction due to its reactivity with silica and alumina in clays. Volcanic and diatom silica have various effects on the strength development of steel slag. As the effects of amorphous silica and the diatom density on the unconfined compressive strength (UCS) and seawater durability of steel slag-treated clays have not been established, this study addressed them. The relationship was confirmed using six steel slag-treated clay samples, air-dried at 20 °C for 28 and 56 days, and three cement- or steel slag-treated clay samples, exposed to seawater for 0, 28, and 90 days. The amorphous silica showed a weak correlation with the UCS, while the diatom density showed a strong relationship with it. No correlation at all was found between the diatom density and the loss on ignition, implicating cyanobacteria as the potential cause of the UCS reduction. Further research is needed to investigate the long-term effects of seawater exposure on the durability of both cement-treated and steel slag-treated clays, given that a correlation has been found between a decrease in UCS with a lower diatom density in cement-treated clays, but not in steel slag-treated clays.